ANALISIS TANTANGAN PEMBELAJARAN BIOLOGI: KENDALA GURU DALAM MENGIMPLEMENTASIKAN MODEL PEMBELAJARAN DI MAN 1 MEDAN - Putri Aldina Harahap, Elis; Umayra; Irene Purba, Helga; Meuthya Reayani Padang , Alya; Arwita, Widya; Mukra, Rizal (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Biology teaching plays a vital role in developing students’ critical and analytical thinking skills, as well as their problem-solving abilities. However, the implementation of innovative teaching models and the use of teaching aids in schools still face various challenges. This study aims to analyse the application of biology teaching models, the use of teaching aids, and the challenges faced by teachers at MAN 1 Medan. This study employs a qualitative approach of a descriptive nature. Data collection was carried out through structured interviews with biology teachers as the main informants, supported by documentation. Data analysis was conducted through the stages of data reduction, grouping, data presentation, and drawing conclusions, with validity testing using triangulation. The research findings indicate that teachers have implemented various teaching models such as Problem-Based Learning (PBL), inquiry-based learning and group discussions, and have consistently used question-and-answer sessions to assess pupils’ understanding. The teaching aids used include PowerPoint presentations, educational videos, visual aids such as human torsos and skeletons, and mobilebased quizzes. However, the implementation of learning has not been optimal due to limited facilities, low student engagement, differences in ability and motivation to learn, and limited learning time. Teachers have attempted to overcome these constraints through a variety of methods, the provision of motivation, and the use ofbavailable media. Therefore, improvements to facilities and the development of technology-based learning innovations are required to enhance the effectiveness of biology learning.